The impact of technological innovation on transport carbon emission efficiency in China: Spillover effect or siphon effect? - Ma, Qifei; Jia, Peng; Kuang, Haibo (Frontiers in Public Health, 2022)
Whether the impact of technological innovation on transport carbon emission efficiency (TCEE) has spillover or siphon effects is currently unclear. Therefore, this paper develops a spatial econometric model to investigate the spatial effect of technological innovation on TCEE. Taking 30 provinces in China as examples, we discover that the TCEE and the technical innovation index have similar evolution characteristics (numerical value increases, the gap widens), and that both have a spatial distribution that decreases from the eastern coast to the western inland. Further research shows that TCEE has a considerable siphon effects in China. The higher the TCEE, the stronger the siphon effect. Although technology innovation has the potential to improve TCEE in local province, the siphon effect prevents TCEE improvement in surrounding provinces. Furthermore, heterogeneity research reveals that excessive government intervention will inhibit the promotion of technological innovation on TCEE. The central and western regions, which have a higher level of government intervention than the eastern region, have more visible inhibitory effects. The findings show that economic growth and transport structure have played an intermediary role in the process of technological innovation promoting TCEE. Regional collaboration and less local protectionism can help the government achieve the dual goals of technological innovation development and TCEE promotion.